A cross-sectional survey on antibiotic use practices in semi-intensive chicken production systems in Thai Nguyen, Vietnam - Yen Luu-Thi-Hai; Huyen Nguyen-Xuan; Sinh Dang-Xuan; Unger, Fred; Muloi, Dishon; Vinh Le-Dac; Nga Tran-Thi-Thuy; Hung Nguyen-Viet; Moodley, Arshnee (International Livestock Research Institute, 2024)
This study highlights knowledge, perception and practices as the drivers of antimicrobial use among farmers in small- and medium-scale households in Thai Nguyen, Vietnam. The findings can be used to develop recommendations and design interventions to promote more cautious use of antimicrobials, thus preventing the impact of antimicrobial resistance.